Implementation of Home Automation System Using OpenHAB Framework for Heterogeneous IoT Devices - Parocha, Raymark C (Archīum Ateneo, 2019)
Recent years has seen the growth in home automation industry as it becomes more accessible due to the increasing dependence on smartphones and smart devices. Despite this, problems in interoperability still exists due to the absence of standardized protocol in the application layer which prompts the user to be dependent on multiple applications to access and monitor several smart appliances. In this study, a home automation system was implemented using OpenHAB framework that is focused on the integration of different smart devices and back-end technologies. Since most smart devices have different communication protocols, the focus of this work was on the development a smart home solution framework that is modular and flexible. In addition, this smart home framework utilized RESTful protocol to integrate smart devices such as smart bulb, smart plug, smart TV from various manufacturers and utilized MQTT protocol to integrate sensors based on ESP8266 that monitors the ambient condition of the room. Lastly, the study provides a comparative analysis on the developed smart home framework and the commercially available smart home solution by Samsung known as SmartThings. The study considered the comparison of these two frameworks in categories such as user-friendliness, security, and their degree of compatibility with various smart devices.